SPEECH PAUSES IN STUDENTS’ PRESENTATION - Suryanovika, Citra (IKIP PGRI Pontianak, 2016)
The study entitled Speech Pauses in Students’ Presentation is designed to find out types of pause produced by third-semester students, and to describe the factors affecting pause. It uses descriptive qualitative research applying Dardjowidjojo theories. The research presented types of pauses, and the factors influencing the production of speech pauses by third-semester students, particularly thirty-three students (aged 18-28 years old). There were two types of pauses made by the third-semester students of School of Foreign Language Pontianak, particularly silent pause and filled pause. The data analysis showed that silent pause was made by 27,3% of students, and filled pause was made by 57,6% of students. Meanwhile, only 15,1% of students who didn’t make any pauses because they read their note whole time. Briefly, silent and filled pauses made by the students because of less preparation, nervousness, lack of lexical knowledge, and distraction. Keywords: speech pause, silent pause, filled pause.